Static and Dynamic Coupled Fields in Bodies with Piezoeffects or Polarization Gradient - Nowacki, Jerzy (Lecture Notes in Applied and Computational Mechanics, 2006)
This monograph book is devoted to the theory of coupled electro-magneto-thermo-elastic fields excited in different bodies by various sources, both static and dynamic. It presents the classical piezoelectric and piezomagnetic effects, the Mindlin's electroelastic coupling due to a polarization gradient, and different combinations of these effects with thermoelasticity. It introduces the basic concepts and equations for the theories of electro- and magneto-mechanical couplings due to piezoeffects and polarization gradient and extends the existing dislocation theory for various cases and geometries.